Analisis Pengaruh Experiential Marketing terhadap Loyalitas Pelanggan melalui Kepuasan Pelanggan sebagai Variabel Intervening: - Agung Irsyad Trilaksono; Budi Prabowo (LPPM Institut Nasional Laa Roiba Bogor, 2023)
This study aims to determine: (1) the effect of experiential marketing on Gojek customer satisfaction; (2) the effect of experiential marketing on Gojek customer loyalty. The population of this study are consumers who have used the Gojek application in the Surabaya area. The number of samples in this study were 100 respondents. The sampling technique was purposive sampling with the criteria of consumers aged ± 17 years and over and had used the Gojek application service more than once in the Surabaya area. Data analysis technique using Partial Least Square with software smartPLS 3.0. The results of this study indicate that experiential marketing has a positive and significant effect on customer satisfaction. Likewise, experiential marketing has a positive and significant effect on customer loyalty. indirectly experiential marketing has a positive and significant effect on customer loyalty through customer satisfaction. Keywords: Experiential Marketing, Customer Satisfaction, Customer Loyalty.